LEARNING VISION DI SEKOLAH UNGGUL - Istiningsih, Viyani (Jurnal Visi Ilmu Pendidikan, 2025)
An important dimension for building an effective school in realizing quality education is vision. Learning vision is a set of visions consisting of mission, goals, superior programs and school student profiles which are implemented through various activities to produce graduates according to the school's vision. Qualitative research approach with a case study at SMA Pangudi Luhur Van Lith Muntilan, Central Java. Data were collected through interviews with informants, a school principal and four deputy principals and teachers as well as observations of the school environment. The results of the interviews are summarized and presented descriptively which explains five essential aspects in implementing learning vision such as: the urgency of learning vision, the idea of establishing a school, the figures who built the vision, learning vision being a driver of superior human resources, and learning vision being the strength of people's involvement in building schools in excellent schools.